The inverse forecast effect - Clarke, David; Blake, Holly (Select Press, 1997)
Social behaviour depends crucially on the way events are linked over time, and on how these linkages are perceived. From a given event, people may be able to infer what followed, or what preceded it. However these two tasks are not as similar as they may seem. Two experiments are reported in which participants had to infer subsequent events given earlier ones, or else the reverse. Performance was consistently more accurate when working ‘backwards’. We call this the ‘inverse forecast effect’. It raises issues about the strategies people use to predict and understand everyday events, and about just how the future is formed from the past.